A study on range of hip and knee motion in normal individuals performing muslim prayers - Thangaraju , Siva (2010)
INTRODUCTION There are 1.6 billion Muslims in the world, and the act of praying represent a paramount and fundamental activity of daily living in their community. They need to adopt several postures that require deep flexion of knee and hip joints to carry out this daily ritual. The increased demand in the range of motion for the lower limb joints has been a focus of interest, in the improvement of arthroplasty implants. This will allow an individual to carry out their responsibility as a Muslim and be well received in this society. However, there is a lack of data on normative range of motion studies for the knee and hip joint during Muslim prayers. The intention of this study was to simultaneously obtain normative passive range of flexion data and the functional range of flexion during Muslim prayers in the knee and hip joints of Malay individuals. METHODS A cohort of 127 Malay males aged between 20 and 30 years were recruited in this cross sectional study. Passive range of motion (PROM) and the flexion angle of the knee and hip joints were measured using a standard goniometer. Demographic and the range of motion data were collected. The effects of body mass index (BMI), abdominal circumference (AC) and limb circumferences (LC) on range of motion were analyzed. RESULTS The demographic and range of motion data was tabulated and presented as minimum and maximum range, mean and standard deviation. The passive range of motion for the knee and hip joints in this study was comparable to other existing normative range of motion database. The variables BMI and AC demonstrated a significant correlation with the knee joint (R2= 0.66). Whereas BMI was the only variable showing correlation for the hip joint (R2= 0.49 ). The recorded mean flexion for Muslim prayers was 0.24, 128.52 and 163.59 degrees for the knee during bowing, prostration and sitting respectively. The mean flexion in the hip joint for the said movement was 53.67, 92.52 and 75.15 correspondingly. CONCLUSION The mean (SD) of the passive knee flexion and passive hip flexion were 141.10(6.60) and 122.10(8.70) degrees respectively which are similar to the values reported previously in the literature. The BMI had significant correlation with both the knee PROM as well as the hip PROM, whereas, the abdominal circumference had only significant correlation for the knee PROM. The limb circumference did not have any significant correlation with both the knee and hip PROM. The predictive equation was also obtained by regression analysis to determine the expected degree of flexion in our local population and is included in the study.